Data-aided SIR measurement for closed loop fast TPC suitable for W-CDMA with closed loop transmit diversity - Priantoro, Akhmad Unggul; Mohamad, Masrul Faizal; Okada, Minoru; Yamamoto , Heiichi (2005)
This paper investigates the effect of signal-to-interference ratio (SIR) measurement accuracy exploiting data modulated symbols in SIR-based fast closed loop transmit power control (TPC) considering the application of closed loop transmit diversity mode 1 in wideband code division multiple access (W-CDMA) system. SIR measurement is performed after removing the random data modulation so as to maximize the instantaneous received power. Computer simulation results clarify the advantage of data-aided SIR measurement even in the presence of feedback information (FBI) errors. Further, we also clarified that exploiting data symbols in addition to DPCH pilot symbols exhibits better performance. The data-aided SIR measurement technique is an add-on functionality to the standardized user equipment (UE) so that the adoption shall not affect the operation of commercial systems.